Male Child with Van Wyk-Grumbach's Syndrome and Other Complications of Long-Standing Primary Hypothyroidism: A Case Report - Ahmed Omran; Jing Peng; Biswas Shrestha; Muhammad Usman Ashhab; Fei Yin (Case Reports in Pediatrics)
Primary hypothyroidism in the juvenile population generally leads to retardation of linear growth and delay or even arrest of puberty. However, in rare conditions, children with long-standing hypothyroidism present with signs of Van Wyk-Grumbach's syndrome (VWGS) which include juvenile hypothyroidism, delayed bone age, and pseudoprecocious puberty. We report a rare case of prepubertal male child from Asian origin, presented with long-standing untreated hypothyroidism complicated with VWGS and other complications including obesity, short stature, hepatomegaly, asymptomatic mild pericardial effusion, and pituitary hyperplasia.